A MÍDIA COMO CONTEÚDO PROGRAMÁTICO NA FORMAÇÃO DE PROFESSORES - Anderson dos Santos Carvalho; Aline Madia Mantovani; Tatyane Perna Silva; Pedro Pugliesi Abdalla (Universidade do Oeste Paulista, 2016)
This paper aims to analyze the dissemination of content on physical culture by the media and develop ideas about the training of Physical Education teachers. The media, while diffusing institution information, it uses its power to convey symbolic references to bodily beauty models associated with notions of health are not always consistent with the reality of the majority of the population, spreading the elements of physical culture as a major means for this purpose. Being a local school for building/dissemination of knowledge, it is up to their teachers analyze such media messages and work with students in order to question them and relates them to the best reality brought. Thus, training courses for teachers in Physical Education are the gateway to the start of this type of questioning, enabling subjects to access the theoretical elements so that they can reflect on the information and images transmitted by the media, including mainly the spectacle of the sport, this study focus. As above, the foregoing discussion is of fundamental importance for the future teachers have access to knowledge about how the information related to the body and bodily practices are produced and disseminated in society today. Consequently, these individuals may perform a reading quality content circulating in the media through put and may have a different future role in society, against standards of beauty, health and pre-established body.